Electrochemical synthesis of enaminones via a decarboxylative coupling reaction. Issue 14 (3rd July 2019) - Kong, Xianqiang; Liu, Yulong; Lin, Long; Chen, Qianjin; Xu, Bo
Abstract : Metal-free and oxidant-free n -Bu4 NI as a redox catalyst and electrolyte. Abstract : An environmentally benign and efficient electrochemical synthesis of enaminones via a decarboxylative coupling reaction of α-keto acids using n -Bu4 NI as a redox catalyst and electrolyte under constant current electrolysis in an undivided cell is reported. A broad vinyl azide substrate scope and high functional group tolerance are observed. A gram-scale reaction further demonstrates the practicability of the protocol. The results of cyclic voltammetry and control experiments indicate that I2 is likely the active species to initiate the oxidative decarboxylation via an acyl hypoiodite intermediate.